Heterogeneity of asthma and the risk of celiac disease in children - Patel, Bhavisha (Allergy Asthma Proc, 2018)
BACKGROUND: Although human leukocyte antigen (HLA)-DR and HLA-DQ genes and gluten play crucial roles in developing celiac disease (CD), most patients with these risk factors still do not develop CD, which indicates additional unrecognized risk factors. OBJECTIVE: To determine the association between asthma and the risk of CD in children. METHODS: We conducted a population-based retrospective case-control study in children who resided in Olmsted County, Minnesota. We identified children with CD (cases) between January 1, 1997, and December 31, 2014, and compared these with children without CD (controls) (1:2 matching). Asthma status was ascertained by using the predetermined asthma criteria (PAC) and the asthma predictive index (API). Data analysis included conditional logistic regression models and an unsupervised network analysis by using an independent phenome-wide association scan (PheWAS) data set. RESULTS: Although asthma status as determined by using PAC was not associated with the risk of CD (odds ratio [OR] 1.4 [95% confidence interval CI, 0.8–2.5]; p = 0.2), asthma status by using the API was significantly associated (OR 2.8 [95% CI, 1.3–6.0]; p = 0.008). A subgroup analysis indicated that children with both asthma as determined by using PAC and a family history of asthma had an increased risk of CD compared with those without asthma (OR 2.28 [95% CI, 1.11–4.67]; p = 0.024). PheWAS data showed a cluster of asthma single nucleotide polymorphisms and patients with CD. CONCLUSION: A subgroup of children with asthma who also had a family history of asthma seemed to be at an increased risk of CD, and, thus, the third factor that underlies the risk of CD might be related to genetic factors for asthma. Heterogeneity of asthma plays a role in determining the risk of asthma-related comorbidity.